2019
DOI: 10.15294/biosaintifika.v11i1.17651
|View full text |Cite
|
Sign up to set email alerts
|

Repellent Activity of Waste Extract from Two Local Medicinal Plant Against Rice Weevil (Sitophilus oryzae)

Abstract: In order to find natural and inexpensive bioinsecticides, the active compound of waste extract from two medicinal plants were analyzed. Ethanolic extracts of Amomum cardamomum and Zingiber zerumbet were evaluated under laboratory conditions for their repellency against rice weevil (Sitophilus oryzae, L.). Four extracts concentration were tested in this research, i.e: 25, 50, 75 and 100%. Efficacy was measured based on the response of rice weevil in preference tests using Y Olfactometer Tube, then the results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…It was found that the cinnamon methanol extract showed the highest repellent effect against rice weevils during each exposure times interval (6 h) at a concentration of 10 mg/mL. In another study, when tested with the extract of Amomum cardamomum under various concentrations (25%, 50%, 75%, and 100%), the highest repellence activity on adult rice weevils was observed at the highest concentration (100%) after 1 h treatment time (Widiyaningrum et al, 2019). A comparison of this study proves that increments in time and concentration positively affect the repellency of wood vinegar and other plant extracts which scientifically represents the actions of chemical constituents' present.…”
Section: Repellent Activitymentioning
confidence: 93%
“…It was found that the cinnamon methanol extract showed the highest repellent effect against rice weevils during each exposure times interval (6 h) at a concentration of 10 mg/mL. In another study, when tested with the extract of Amomum cardamomum under various concentrations (25%, 50%, 75%, and 100%), the highest repellence activity on adult rice weevils was observed at the highest concentration (100%) after 1 h treatment time (Widiyaningrum et al, 2019). A comparison of this study proves that increments in time and concentration positively affect the repellency of wood vinegar and other plant extracts which scientifically represents the actions of chemical constituents' present.…”
Section: Repellent Activitymentioning
confidence: 93%
“…A group of plants reported having insecticidal activities are plants from Zingiberaceae family. Studies on secondary metabolite from plant rhizomes reveal that the members of Zingiberaceae which have the potential as a source of natural insecticides are turmeric rhizome (Curcuma longa) 10 , ginger (Officinale zingiber) 11 , cardamom (Amomum cardamomum) 12 , galangal (Alpinia galanga) 13 and bitter ginger (Zingiber zerumbet) 14 . However, the rhizome of medicinal plants generally has high selling value as raw materials for spices and herbal medicines, so they are less economical if used as a source of botanical insecticides.…”
Section: Introductionmentioning
confidence: 99%